Macular microcirculation characteristics in Parkinson's disease evaluated by OCT-Angiography: a literature review. (3rd April 2022) - Christou, Evita Evangelia; Asproudis, Ioannis; Asproudis, Christoforos; Giannakis, Alexandros; Stefaniotou, Maria; Konitsiotis, Spiridon
ABSTRACT: Purpose: Given the fact that retina may provide a window into the central nervous system, there has been interest in identifying retinal biomarkers as predicting factors of pathological processes in neurodegenerative disorders. Emerging evidence has suggested that macular microcirculation changes in Parkinson disease (PD) may indicate the alterations of cerebral microvasculature. The use of Optical Coherence Tomography Angiography (OCT-A) has attracted significant attention in recent years as this technique offers a detailed analysis of the existence of changes at the macular capillary plexus. Methods: A detailed review of the literature was performed in PubMed until June 2021. We identified all papers referring to the alterations of the macular capillary plexus in PD using OCT-A. Results: A comprehensive update indicates that microvasculature alterations of the macular capillary plexus utilizing OCT-A may comprise useful biomarkers regarding the cerebral vasculature in PD. Since the available evidence is limited, additional studies are warranted to establish the OCT-A parameters as predicting factors in clinical practice. Conclusions: A review of the existing literature sheds light on the microvasculature changes of the macular capillary plexus as seen on OCT-A in PD patients. The current article discusses notable aspects of key publications on the topic, highlights the importance of the potential long-term effectiveness of OCT-A biomarkers in PD and proposes the need for further future research.